Questionnaire on Assessing Individual Vulnerability to Cyberbullying: Development and Preliminary Validation - Viktor P. Sheinov (Peoples' Friendship University of Russia (RUDN University), 2020)
Cyberbullying is manifested in repeated deliberate acts of aggression by one or more persons who use electronic means of communication to attack a victim who cannot defend him- or herself. Cyberbullying is a form of violence through harassment, insults, bullying, humiliation or intimidation carried out using the Internet, mobile phones and other electronic devices. Cyberbullying is widespread and causes severe harm to its victims, having a negative impact on their mental and physical health. The purpose of this study is to develop a reliable and valid questionnaire on assessing individual vulnerability to cyberbullying. The article constructs such a questionnaire and proves that it meets the standard reliability criteria: internal consistency, homogeneity and retest reliability. It is shown that the questionnaire is valid and satisfies the key validity criteria: validation in the process of designing the questionnaire, substantive, constructive and convergent validity. The questionnaire is standardised, the norms for young men and women are given, presented in average values and standard deviations. The theoretical basis of the study is the model of manipulative influence (which includes cyberbullying) and the psychological mechanism of cyberbullying described by this model. Confirmatory factor analysis showed that the model of the presented questionnaire has good indicators of reliability and statistical consistency. The experimental part of the study involved 307 young men and women at the ages from 17 to 21 years old - students of medical colleges and cadets of the University of the Ministry of Emergencies. The study included two stages of psychodiagnostics of the subjects carried out with an interval of two months. The states of individuals vulnerable to cyberbullying, identified using the questionnaire, are consistent with the results obtained in previous studies. The proposed questionnaire makes it possible to warn an individual about the existing or threatening danger of becoming a victim of cyberbullying. The questionnaire can stimulate the study of cyberbullying in the Russian-speaking society and, in particular, in cross-cultural studies.